(untitled) (Global Journal of Science Frontier Research, 2012)
One Hundred and fifty (150) 7 day-old broilers under conditions of heat stress were randomly assigned to 3 dietary treatments of 3 replicates each. There were 10 birds in each replicate. The 3 diets were: Diet 1 – Control diet (without Chromium supplementation); Diet 2 - 0.15mg/kg Chromium supplementation and Diet 3 - 0.25mg/kg Chromium supplementation. The inorganic Chromium source was Chromium chloride. The aim of the study was to evaluate the effect(s) of heat stress on the intestinal mucosa of broilers. The study lasted 7 weeks and data on performance (feed intake, weight gain and feed conversion ratio) and intestinal morphology (villus height and crypt depth) were taken. Data taken were subjected to statistical analysis of variance (ANOVA) procedure of SAS 2010. Significant differences were observed in the weight gain with the birds fed diet 3 having the highest mean value of 45.00g/day and the least value of 40.00g/bird for birds the on control diet. However, birds fed diet 3 (0.25mg/kg) had the least significant feed conversion ratio 2.00 when compared with birds on control diet (2.25) and diet 2 (2.14). The villus height in the ileum of birds on Diet 3 was significantly (p < 0.05) taller than that of birds on the other diets while the villus height in the jejunum of birds on Diet 1 was significantly (p < 0.05) taller than that of birds on the other diets.